Female gender disadvantage and its impact on Psychological morbidity: A cross- sectional study among married Indian rural women of child bearing age - Langer, Bhavna; Kumari, Rashmi; Gupta, Riya; Mahajan, Richa; Gupta, Rajiv Kumar; Langer, Raja (Indian Journal of Community Health, 2021)
Background-Male preference is deeply entrenched in the society. Gender disadvantage predisposes to limited education, employment opportunities and healthcare. Aims and objectives: To assess the Gender disadvantage in rural married females and its impact on their psychological morbidity. Methodology: Analytical Cross sectional study was conducted in a randomly selected village of a rural health block. All the eligible women were interviewed using Door Knock Procedure. Psychological morbidity was assessed using 20 items Self Rating Questionnaire (SRQ-20). Statistical Analysis: Data was analysed using SPSS ver 20.0. Tests of significance applied were Chi square test and ANOVA. P value of <0.05 was considered to be statistically significant. Results: Prevalence of Female gender disadvantage was 59.89%. Parental male predisposition and socioeconomic status were found to be statistically associated (p<0.05). The women’s own preference for a male child was strongly predicted by their own gender disadvantage from the parents. Statistically significant difference in psychological morbidity was found amongst women who had both parental male predisposition and lack of empowerment in comparison to those who did not have these (p=0.00). Conclusion: Psychological morbidity due to gender disadvantage is a cause of concern. Social awareness and strongly enforced laws like PC-PNDT can reduce these preferences.